2011
DOI: 10.1108/s2044-9968(2011)0000001016
|View full text |Cite
|
Sign up to set email alerts
|

Social annotation to enhance learning and assessment in higher education

Abstract: Social annotation products make the thinking of learners transparent, visible, and easily accessible for sharing with others, self-reflection, and feedback. This is accomplished by enabling almost any number of users to have threaded discussions linked to selected sections of a page. Three professors share their experiences with the use of a social annotation product, HyLighter, to enhance teaching, learning and assessment activities in three different areas of the college curriculum. One teaches screenplay wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Over the course of the subsequent decades, a profusion of social annotation tools has been developed and studied. These tools, including WebAnn (Brush et al, 2002), HyLighter (Lebow et al, 2011), EDUCOSM (Nokelainen et al, 2003), eLAWS (Glover et al, 2007), PAMS 2.0 (Su et al, 2010), and many more, helped progressively refine how a social annotation system might best work in different contexts and for different purposes, including education. Wolfe (2008) has summarized the results of this phase of development as follows.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the course of the subsequent decades, a profusion of social annotation tools has been developed and studied. These tools, including WebAnn (Brush et al, 2002), HyLighter (Lebow et al, 2011), EDUCOSM (Nokelainen et al, 2003), eLAWS (Glover et al, 2007), PAMS 2.0 (Su et al, 2010), and many more, helped progressively refine how a social annotation system might best work in different contexts and for different purposes, including education. Wolfe (2008) has summarized the results of this phase of development as follows.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The discussions with SA are more dynamic than static, and the contributions are anchored to the required reading (Brown & Croft, 2020). Lebow et al (2011) found that SA fostered self-efficacy in students and improved the quality of instruction for faculty. It promotes both student-to-student and instructor-to-student interactions.…”
Section: What Is Social Annotation?mentioning
confidence: 97%
“…The picture recovery system efficiency will need to be used. Using Precision @ Q, image ranking in the return list will typically be evaluated using accuracy at a retrieval of the suggested technique than the Guided LDA [38].…”
Section: Methodsmentioning
confidence: 99%